INVESTIGATION OF ALPHA DECAY HALF-LIFE USING QUANTUM TUNNELING MODELS IN HEAVY NUCLEI - Kareem, N.M.; Khalaf, Saif Ali J.; Khalf, Ya.S.; Ahmed, E.M. (Eurasian Physical Technical Journal, 2026)
Alpha decay half-lives of selected heavy and superheavy nuclei with atomic number greater than 82 are systematically investigated using three quantum tunneling approaches. The calculated half-lives are compared with evaluated experimental data compiled in international nuclear data libraries. The predictive performance of each approach is assessed using the root-mean-square deviation of the logarithm of half-life values. The analysis indicates that the model based on Coulomb interaction with nuclear surface proximity effects provides the closest overall agreement with experimental values, with a deviation of 0.46 in logarithmic units. The unified fission-type approach shows intermediate agreement with a deviation of 0.63, while the semiclassical tunneling approximation shows the largest deviation of 0.88. These results highlight the importance of including nuclear surface proximity effects in barrier penetration calculations for reliable prediction of alpha-decay lifetimes in heavy and superheavy nuclei.